Hypoglycemic effect of the ethyl acetate fraction of Chrysophyllum cainito L. leaves on streptozotocin-nicotinamide-induced diabetic and pre-diabetic rats - Rocas, Blaire Justine S.​; Dacalos, Candelen P.​; Tuibeo, Noreen Vera F.​; Yu, Raymond Fernando B.​ (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Diabetes mellitus is a chronic condition characterized by increased levels of glucose in the blood, due to either diminished production of insulin or decreased insulin sensitivity. Type 2 Diabetes is one of the two classifications of this condition -- characterized by insulin resistance and is the most common form, usually acquired due to genetic factors or poor lifestyle habits. One of the treatments for this type of diabetes is the alpha-glucosidase inhibitor. Alpha-glucosidase inhibitors are oral enzyme inhibitors that do not act in the pancreas, but instead work by delaying carbohydrate absorption, specifically, by competitive and reversible inhibition of intestinal alpha-glucosidases, resulting to a delay in carbohydrate digestion, prolonging the overall carbohydrate digestion time, and thus reducing the rate of glucose absorption. This alpha-glucosidase inhibition is also manifested by the Chrysophyllum cainito L. plant. Commonly known as Caimito, the leaves of this plant are traditionally used to decrease blood sugar as it was found to contain alkaloids, flavonoids, polyphenols, and carbohydrates. Previous diabetic researches reported that the alkaloids stimulate hepatic glycogenesis, while flavonoids are known to be bioactive antidiabetic principles. Several studies about the hypoglycemic properties of this plant have already been reported. However, the in vivo activity of its crude Ethanolic extract is still inexistent. With that, this study aimed to evaluate the hypoglycemic activity of the ethyl acetate fraction of the leaves of C. cainito. This was obtained by administering the ethyl acetate fraction to Streptozotocin-Nicotinamideinduced diabetic and pre-diabetic rats. Postprandial blood glucose levels were observed thereafter. Results showed that the Ethyl Acetate fraction manifested significant (p<0.05) reduction in the postprandial increase of blood plasma glucose.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2017.
Keywords: Sapotaceae; Chrysophyllum cainito; Caimito